Sosialisasi Kontrol Diri dalam Menekan Perilaku Konsumtif Remaja di SMA Swasta Nasional Petatal - Wulandari, Rizki; Triastuti, Neni; Siregar, Nurul Hikmatul Alawiyah; Sariani, Sariani (CV. IRA PUBLISHING, 2025)
Technological advancement has brought ease to all segments of society, particularly in shopping and fulfilling various needs and desires through online shop platforms and social media. These developments have had both positive and negative impacts, especially on adolescents. Teenagers are particularly vulnerable to consumptive behavior when shopping, a phenomenon observed at SMA Swasta Nasional Petatal in Batu Bara Regency. Most adolescents experience consumptive behaviors due to a lack of self-control. This community service initiative aims to provide knowledge, understanding, and skills regarding self-control of consumptive behavior. Through collaboration with various stakeholders, the program was successfully implemented and achieved its objectives.